Erosion of an active fault scarp leads to drainage capture in the Amazon region, Brazil - Val, Pedro; Silva, Clauzionor; Harbor, David; Morales, Norberto [UNESP]; Amaral, Felipe; Maia, Tiago (Wiley-Blackwell, 2014)
Far from the continental margin, drainage basins in Central Amazonia should be in topographic steady state; but they are not. Abandoned remnant fluvial valleys up to hundreds of square kilometers in size are observed throughout Amazonia, and are evidence of significant landscape reorganization. While major Late Miocene drainage shifts occurred due to initiation of the transcontinental Amazon River, local landscape change has remained active until today. Driven either by dynamic topography, tectonism, and/or climatic fluctuations, drainage captures in Amazonia provide a natural experiment for assessing the geomorphic response of low-slope basins to sudden, capture related base-level falls. This paper evaluates the timing of geomorphic change by examining a drainage capture event across the Baependi fault scarp involving the Cuieiras and TarumA-Mirim River basins northwest of the city of Manaus in Brazil. A system of capture-related knickpoints was generated by base-level fall following drainage capture; through numerical modeling of their initiation and propagation, the capture event is inferred to have occurred between the middle and late Pleistocene, consistent with other studies of landscape change in surrounding areas. In low-slope settings like the Amazon River basin, base-level fall can increase erosion rates by more than an order of magnitude, and moderate to large river basins can respond to episodes of base-level fall over timescales of tens to hundreds of thousands of years. Copyright (c) 2013 John Wiley & Sons, Ltd.
Keywords: Amazonia; response time; drainage capture; Pleistocene; Baependi fault scarp